Depositional environment of the Laptev Sea (Arctic Siberia) during the Holocene. - Bauch, Henning A; Kassens, Heidemarie; Erlenkeuser, Helmut; Grootes, Pieter Meiert; Thiede, Jörn (PANGAEA, 1999)
The Holocene depositional setting of the Laptev Sea was studied using three marine sediment cores from water depths between 77 and 46 m. Based on sedimentary parameters (TOC content, delta13Corg, sedimentation rates) controlled by radiocarbon age models the palaeoenvironment of a strongly coupled river-shelf system was reconstructed since ~11 ka BP. Caused by a transgressing sea after the last glaciation, all cores reveal progressive decreases in sedimentation rates. Using the sedimentary records of a core from the Khatanga-Anabar river channel in the western Laptev Sea, several phases of change are recognized: (1) an early period lasted until ~10 ka BP characterized by an increased deposition of plant debris due to shelf erosion and fluvial runoff; (2) a transitional phase with consistently increasing marine conditions until 6 ka BP, which was marked at its beginning near 10 ka BP by the first occurrence of marine bivalves, high TOC content and an increase in delta13Corg; (3) a time of extremely slow deposition of sediments, commencing at ~6 ka BP and interpreted as Holocene sea-level highstand, which caused a southward retreat of the depositional centres within the now submerged river channels on the shelf; (4) a final phase with the establishment of modern conditions after ~2 ka BP.
Age determination and sedimentation rates of sediment cores in the Laptev Sea
Keywords: Arctic Ocean; ARK-XI/1; AWI_Paleo; Gravity corer (Kiel type); KAL; Kapitan Dranitsyn; Kasten corer; KD9502-14; Laptev Sea; Paleoenvironmental Reconstructions from Marine Sediments @ AWI; PM9499-2; Polarstern; Professor Multanovskiy; PS2725-5; PS36; PS36/009; Quaternary Environment of the Eurasian North; QUEEN; SL; Transdrift-II; Transdrift-III; VC; Vibro Corer